2021
DOI: 10.1007/s43390-021-00378-4
|View full text |Cite
|
Sign up to set email alerts
|

Identifying complications and failure modes of innovative growing rod configurations using the (hybrid) magnetically controlled growing rod (MCGR) and the spring distraction system (SDS)

Abstract: Background Magnetically controlled growing rods (MCGRs) offer non-invasive distractions in Early-Onset Scoliosis (EOS). However, implant-related complications are common, reducing its cost-effectiveness. To improve MCGRs functionality and cost-effectiveness, we often combine a single MCGR with a contralateral sliding rod (hybrid MCGR). Recently, we developed the spring distraction system (SDS) as an alternative, which provides continuous distraction forces through a helical spring. This study aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 34 publications
2
6
0
Order By: Relevance
“…17,18 A recent complication analysis between SDS and (hybrid) MCGR patients showed that the SDS could not prevent rod fractures when 4.5 mm rods were used. 34 A review of these fractures showed similar points of failure to the locations highlighted by the present study. In several patients with bilateral springs, fractures occurred near the distal anchors, often close to the vicinity of the locking buttress, potentially due to set screw notches that act as stress concentrators.…”
Section: Discussionsupporting
confidence: 81%
“…17,18 A recent complication analysis between SDS and (hybrid) MCGR patients showed that the SDS could not prevent rod fractures when 4.5 mm rods were used. 34 A review of these fractures showed similar points of failure to the locations highlighted by the present study. In several patients with bilateral springs, fractures occurred near the distal anchors, often close to the vicinity of the locking buttress, potentially due to set screw notches that act as stress concentrators.…”
Section: Discussionsupporting
confidence: 81%
“…Moreover, and maybe as a consequence, HRQoL improved, with even better scores one year after implantation compared to pre-implantation. This finding indicates that the implant may be better accepted than the first generation [29]. However, in the current study, fewer patients completed the EOSQ-24 at each follow-up, which could have caused a bias.…”
Section: Discussionmentioning
confidence: 63%
“…In the current study we investigated an iteration of the SDS design, to mitigate materialrelated complications. In addition to good curve control and maintenance of growth, it appeared that the number of SAEs and especially UPRORs diminished compared to the first generation [28,29]. Obviously, as this is a preliminary study, the numbers were low, and a statistical analysis on an underpowered study was not worthwhile.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations